(3QLGd GdWhSjs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3Ydj Hf EOQjSs)
(3ChdgG (B:s
(3GdMeO ddg Mb MeO(B... (3aEfj bO CLHJ Edi eG JcQQ SDGd GdTjN GdaGVd ajg ef LeY cJGH jTJed Ydi CSeGA GdQLGd(B...s
(3BNQgG (B:s
(3HGH GdfSGA(B: (3aGWeI HfJ gGQhf(B... (3YHjO Gddg Hf Ydj GdMdHj hde jSeY efgG ZjQ gPG(B... (3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B84s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B72s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs